A method for identifying suitable biodiversity offset sites and its application to reclamation of coastal wetlands in China. (November 2018) - Yu, Shuling; Cui, Baoshan; Gibbons, Philip
Abstract: We explored the potential for biodiversity offsetting to be applied in regions with considerable development pressure. We developed a method to identify suitable locations for restoration offsets and applied this to coastal reclamation in the Yellow River Delta region of China, an internationally important area for migratory birds, but in which 44% of wetlands have been reclaimed. We evaluated the suitability of sites for offsetting based on their ecological similarity to development sites, the potential of biota to migrate between sites and socio-economic criteria. We predicted that 60–100% of all reclamation in the Yellow River Delta between 1980 and 2015 could be theoretically offset provided no constraints were placed on where offsetting occurs within the region. However, where potential offset sites were constrained to areas with high suitability only 8–15% of historic coastal reclamation could be offset. Spatial options for offsetting also declined where time lags before restoration were longer. Our results indicated that strict in-kind biodiversity offsetting becomes increasingly challenging in highly modified landscapes because of a lack of spatial options for offsets and a tendency for potential offset sites to be dissimilar to the habitat that originally occurred on developed sites in these landscapes. Policies that seek to enable development within highly modified landscapes by providing flexibility for offsetting in space and time risk providing offsets that are ecologically dissimilar from development sites and have limited capacity for biota to migrate to or from them. Our methodology can be used as a planning tool to indicate the level of development within a landscape or region beyond which no net loss is unlikely to be feasible.